Quantitative imaging biomarkers for dural sinus patterns in idiopathic intracranial hypertension. Issue 2 (3rd January 2017) - Zur, Dinah; Anconina, Reut; Kesler, Anat; Lublinsky, Svetlana; Toledano, Ronen; Shelef, Ilan
Abstract: Objective: To quantitatively characterize transverse dural sinuses (TS) on magnetic resonance venography (MRV) in patients with idiopathic intracranial hypertension (IIH), compared to healthy controls, using a computer assisted detection (CAD) method. Materials and Methods: We retrospectively analyzed MRV studies of 38 IIH patients and 30 controls, matched by age and gender. Data analysis was performed using a specially developed Matlab algorithm for vessel cross‐sectional analysis. The cross‐sectional area and shape measurements were evaluated in patients and controls. Results: Mean, minimal, and maximal cross‐sectional areas as well as volumetric parameters of the right and left transverse sinuses were significantly smaller in IIH patients than in controls ( p  < .005 for all). Idiopathic intracranial hypertension patients showed a narrowed segment in both TS, clustering near the junction with the sigmoid sinus. In 36% (right TS) and 43% (left TS), the stenosis extended to >50% of the entire length of the TS, i.e. the TS was hypoplastic. Narrower vessels tended to have a more triangular shape than did wider vessels. Conclusion: Using CAD we precisely quantified TS stenosis and its severity in IIH patients by cross‐sectional and volumetric analysis. This method can be used as an exact tool for investigating mechanisms of IIH development and response to treatment. Abstract : Cross‐sectional analysis of dural transverse sinuses (TS) using computer‐assisted detection (CAD) provides exact quantitative information. Patients with idiopathic intracranial hypertension show significant narrowing of TS compared to controls. CAD analysis appears as a precise tool for investigating mechanisms and responses to treatment in IIH patients.